Characterization of Shiga Toxin 2a Encoding Bacteriophages Isolated From High-Virulent O145:H25 Shiga Toxin-Producing Escherichia coli - Ramstad, Silje N.; Wasteson, Yngvild; Lindstedt, Bjørn-Arne; Taxt, Arne M.; Bjørnholt, Jørgen V.; Brandal, Lin T.; Bohlin, Jon (Frontiers in Microbiology, 2021)
Shiga toxin-producing Escherichia coli (STEC) may cause severe disease mainly due to the ability to produce Shiga toxins (Stx) encoded on bacteriophages. In Norway, more than 30% of the reported cases with STEC O145:H25 develop hemolytic uremic syndrome (HUS) and most cases, with known travel history, acquired the infection domestically. To describe phage characteristics associated with high virulence we extracted the Stx2a phage sequences from eight clinical Norwegian O145:H25 STEC to conduct in-depth molecular characterization using long and short read sequencing. The Stx2a phages were annotated, characterized and compared with previously published Stx2a phages isolated from STEC of different serotypes. The Norwegian O145:H25 Stx2a phages showed high sequence identity (>99%) with 100% coverage. The Stx2a phages were located at the integration site yciD, were approximately 45 kbp long and harboured several virulence associated genes, in addition to stx2a, such as nanS and nleC. We observed high sequence identity (>98%) and coverage (≥94%) between Norwegian O145:H25 Stx2a phages and publicly available Stx2a phages from O145:H25 and O145:H28 STEC, isolated from HUS cases in USA and a hemorrhagic diarrhea case from Japan, respectively. However, low similarity was seen when comparing the Norwegian O145:H25 Stx2a phage to Stx2a phages from STEC of other serotypes. In all the Norwegian O145:H25 STEC we identified a second phage or remnants of a phage (a shadow phage, 61 kbp) inserted at the same integration site as the Stx2a phage. The shadow phage shared similarity with the Stx2a phage, but lacked stx2a and harboured effector genes not present in the Stx2a phage. We identified a conserved Stx2a phage among the Norwegian O145:H25 STEC which shared integration site with a shadow phage in all isolates. Both phage and shadow phage harboured several virulence associated genes which may contribute to the increased pathogenicity of O145:H25 STEC.